2 Systemic glucocorticoids and bradycardia in critically ill children: a retrospective study. (19th August 2020) - Maltais-Bilodeau, Camille; Frenette, Maryse; Morissette, Geneviève; Bailey, Dennis; Cloutier, Karine; Laberge, Camille; Simonyan, David
Abstract: Background: Glucocorticoids are widely used in the pediatric population. They are associated with numerous side effects including repercussions on the cardiovascular system. The impact on heart rate is not well known, but bradycardia has been reported, mostly with high doses. Objectives: We described the occurrence of bradycardias and the variation of heart rate in critically ill children receiving glucocorticoids. Design/Methods: We conducted a retrospective study including 1 month old to 18 year old children admitted to the Pediatric Intensive Care Unit between 2014 and 2017, who received a glucocorticoid dose equivalent to 1 to 15 mg/kg/day of prednisone. We collected data on exposition to glucocorticoids, heart rate before, during and after the exposition, and interventions from the medical staff in response to bradycardia. The primary outcome was the occurrence of bradycardia and the secondary outcomes were the magnitude of heart rate variation and the clinical management of bradycardias. Results: We included 92 admissions (85 patients). The median dose of glucocorticoid used was 2.80 mg/kg/day of prednisone (2.08—3.80). We found 70 cases (76%) with at least one bradycardia. Before treatment, all patients had a mean heart rate higher than the 5th percentile for age. During exposition to glucocorticoids, 8 patients (10%, n = 83) had a median heart rate ≤ 5th percentile. We noted 46 cases of bradycardia (50%) that led to an intervention from the medical staff, but no patient had a major event associated to bradycardia. We found a significant association between bradycardia and age (estimate -0.136, 95% CI -0.207—-0.065, p < 0.001), glucocorticoid dose (estimate 4.820, 95% CI 2.048—7.592, p < 0.001) and intravenous administration (estimate 8.709, 95% CI 1.893—15.524, p = 0.012). Conclusion: In our study, most children hospitalized at the intensive care unit receiving standard doses of glucocorticoid experienced bradycardia. The majority of episodes led to an intervention from the medical staff. Presence of bradycardia was associated with younger age, higher dose and IV administration of glucocorticoids.